2014
DOI: 10.1017/s0142716414000551
|View full text |Cite
|
Sign up to set email alerts
|

The impact of first language background and visual information on the effectiveness of low-variability input

Abstract: This study investigated whether first language (L1) background and visual information impact the effectiveness of skewed and balanced input at promoting pattern detection. Participants (N = 84) were exposed to Esperanto sentences with the transitive construction under skewed (one noun with high token frequency) or balanced (equal token frequency) input conditions while viewing either color or black-and-white visuals. Their ability to detect the relevant morphological and syntactic features of the transitive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 29 publications
(38 reference statements)
1
27
1
Order By: Relevance
“…Prior construction learning studies (Boyd, Gottschalk, and Goldberg 2009;Casenhiser and Goldberg 2005;Goldberg and Casenhiser 2008;Goldberg, Casenhiser, and Sethuraman 2004;Goldberg, Casenhiser, and White 2007) have shown that English L1 speakers can comprehend and produce the novel construction of appearance (N 1 N 2 V), with the corresponding meaning of N 1 "appears in/on" N 2 (e.g., the spot the king moopoed) after relatively brief exposure. In contrast, construction learning studies with L2 English speakers reported greater difficulty in detecting a variety of constructions, including the appearance construction and the Samoan ergative construction (Nakamura 2012), English dative constructions (McDonough and Nekrasova-Becker 2014;Year and Gordon 2009), and Esperanto transitives (Fulga and McDonough 2014;McDonough and Fulga 2015;McDonough and Trofimovich 2013). For example, only about one-fifth of all Thai participants tested by McDonough and Trofimovich (2013) were able to detect the Esperanto transitive construction.…”
Section: Challenges In Detecting Novel Constructionsmentioning
confidence: 84%
See 1 more Smart Citation
“…Prior construction learning studies (Boyd, Gottschalk, and Goldberg 2009;Casenhiser and Goldberg 2005;Goldberg and Casenhiser 2008;Goldberg, Casenhiser, and Sethuraman 2004;Goldberg, Casenhiser, and White 2007) have shown that English L1 speakers can comprehend and produce the novel construction of appearance (N 1 N 2 V), with the corresponding meaning of N 1 "appears in/on" N 2 (e.g., the spot the king moopoed) after relatively brief exposure. In contrast, construction learning studies with L2 English speakers reported greater difficulty in detecting a variety of constructions, including the appearance construction and the Samoan ergative construction (Nakamura 2012), English dative constructions (McDonough and Nekrasova-Becker 2014;Year and Gordon 2009), and Esperanto transitives (Fulga and McDonough 2014;McDonough and Fulga 2015;McDonough and Trofimovich 2013). For example, only about one-fifth of all Thai participants tested by McDonough and Trofimovich (2013) were able to detect the Esperanto transitive construction.…”
Section: Challenges In Detecting Novel Constructionsmentioning
confidence: 84%
“…The findings of previous L2 research (Hopp 2010;Jiang 2004Jiang , 2007Papadopoulou et al 2011), including research on novel construction learning (Fulga and McDonough 2014;McDonough and Fulga 2015;McDonough and Trofimovich 2013), suggest that it might be difficult for L2 learners to detect and use a novel morphological cue for sentence interpretation. The current set of findings further qualifies this challenge by suggesting that structural priming, in the absence of any other input, feedback, or output learning opportunities, provides little evidence to help learners abandon a familiar cue in favor of a new one.…”
Section: Discussionmentioning
confidence: 97%
“…In Goldberg et al. (), the skewed verb occurred 8 times, in Zhang & Ma () 7 times, in McDonough & Nekrasova–Becker () 8 times, in McDonough & Trofimovich () 12 times, and in Fulga & McDonough () 15 times. However, in Year & Gordon (), it was 24 times.…”
Section: Introductionmentioning
confidence: 98%
“…McDonough and Trofimovich () compared the role of balanced and Zipfian input in facilitating the Thai EFL learners’ acquisition of the Esperanto transitive construction under both inductive and deductive instructions, finding that only the group exposed to the balanced, deductive input instructions detected the novel pattern. Likewise, Fulga and McDonough () investigated whether L1 background and visuals (color vs. black‐and‐white) impact the effect of skewed and balanced input at promoting pattern detection of Esperanto transitives. No reliable effect of visuals or skewed input, but a significant effect of the L1 on learners’ detection of the novel pattern was observed.…”
Section: Introductionmentioning
confidence: 99%
“…CONSTRUCTION LEARNING STUDIES CARried out by Goldberg and colleagues have shown that first language (L1) speakers of English can comprehend and produce the novel construction of appearance (N 1 N 2 V), with the corresponding meaning of N 1 ‘appears in/on’ N 2 (e.g., the spot the king moopoed ) after relatively brief language exposure (Boyd, Gottschalk, & Goldberg, ; Casenhiser & Goldberg, ; Goldberg & Casenhiser, ; Goldberg, Casenhiser, & Sethuraman, ; Goldberg, Casenhiser, & White, ). However, construction learning studies with second language (L2) speakers have reported far greater variability with a variety of constructions, including the appearance construction and Samoan ergative constructions (Nakamura, ), Esperanto transitives (Fulga & McDonough, ; McDonough & Fulga, ; McDonough & Trofimovich, , ), and English datives (McDonough & Nekrasova–Becker, ; Year & Gordon, ). These studies have shown that L2 speakers experience considerable difficulty when learning new patterns.…”
mentioning
confidence: 99%